PENGARUH PEMBERIAN JUMLAH TAKARAN RAGI TERHADAP KANDUNGAN PROTEIN YANG DIHASILKAN PADA TEMPE BIJI NANGKA (Artocarpus heterophyllus) - Harmoko, Harmoko; Sutanto, Agus; Sari, Kartika (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
Jackfruit (Artocarpusheterophyllus), is well known in Indonesia, when the fruit is ripe jackfruit can be consumed. After we consume jackfruit, well leave the trash in the form of jackfruit seed, which has not been used by the community to the fullest. The purpose of this study are trying to explore another potential of jackfruit seeds and increasing the protein content of jackfruit seeds by processing in to tempeh. Another purpose is knowing the number yeast of doses that can produce in tempeh of jackfruit seeds. This research uses 4 treatments (A: 0.25 grams yeast/50 grams jackfruit seed, B: 0.50 grams yeast/50 grams jackfruit seeds, C: 0.75 gram yeast/50 grams jackfruit seeds, and D: 1 grams yeast/50 grams of jackfruit seeds) with 4 repetitions. Test protein content tests conducted at the Laboratory of Food Technology and Agricultural Faculty of Agricultural Technology, GadjahMada University (UGM). Treatment A produced protein average of 2,64%, B produced protein average of 3,429%, treatment C produced protein average of 4,146% and treatment D produced protein average of 5,635% protein. The highest protein content is produced by treatment D.Keywords: Takaran ragi, tempe biji nangka (Artocarpusheterophyllus),kandungan protein.